A. \(\frac{{x - 2}}{1} = \frac{{y - 2}}{1} = \frac{z}{1}\)
B. \(\frac{x}{1} = \frac{{y - 2}}{1} = \frac{z}{1}\)
C. \(\frac{x}{1} = \frac{{y - 3}}{{ - 1}} = \frac{{z - 1}}{1}\)
D. \(\frac{x}{1} = \frac{{y - 3}}{{ - 1}} = \frac{{z - 1}}{1}\)
B
Do \(d\) cắt \({d_1},{d_2},{d_3}\) lần lượt tại \(A,B,C\) nên \(A\left( {t;4 - t; - 1 + 2t} \right),B\left( {t';2 - 3t'; - 3t'} \right),C\left( { - 1 + 5t'';1 + 2t''; - 1 + t''} \right)\).
Lại có \(AB = BC \Rightarrow B\) là trung điểm của \(AC\) \( \Leftrightarrow \left\{ \begin{array}{l}{x_B} = \frac{{{x_A} + {x_C}}}{2}\\{y_B} = \frac{{{y_A} + {y_C}}}{2}\\{z_B} = \frac{{{z_A} + {z_C}}}{2}\end{array} \right.\)
\( \Leftrightarrow \left\{ \begin{array}{l}t' = \frac{{t - 1 + 5t''}}{2}\\2 - 3t' = \frac{{4 - t + 1 + 2t''}}{2}\\ - 3t' = \frac{{ - 1 + 2t - 1 + t''}}{2}\end{array} \right.\) \( \Leftrightarrow \left\{ \begin{array}{l}2t' = t + 5t'' - 1\\4 - 6t' = 5 - t + 2t''\\ - 6t' = - 2 + 2t + t''\end{array} \right.\) \( \Leftrightarrow \left\{ \begin{array}{l}t = 1\\t' = 0\\t'' = 0\end{array} \right. \Rightarrow \left\{ \begin{array}{l}A\left( {1;3;1} \right)\\B\left( {0;2;0} \right)\\C\left( { - 1;1; - 1} \right)\end{array} \right.\)
Đường thẳng \(d\) đi qua điểm \(B\left( {0;2;0} \right)\) và nhận \(\overrightarrow {BA} = \left( {1;1;1} \right)\) làm VTCP nên \(d:\frac{x}{1} = \frac{{y - 2}}{1} = \frac{z}{1}\).
Chọn B.
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247